Arctic shipping: a study on the impacts of northern sea route on Singapore's status as an international maritime centre - Gee, Song Xi (2014)
In recent years, global warming has taken its toll on the livelihood of millions across the world. Even the coldest regions in the world are not spared of climate changes. The greenhouse effect has caused warmer and longer summers in the Arctic region. This has resulted in substantial melting of ice caps; paving the way for shipping across the Northern Sea Route which was once not navigable commercially. It is said that shipment across the Northern Sea Route will reduce the operation cost by 30 percent. Hence, the popularity towards Arctic shipping may accelerate within the next 10-20 years, resulting in a change in shipping patterns. Singapore’s position as an International Maritime Centre may be affected in view of the change in global shipping patterns. This is exemplified by Singapore’s entry into the Arctic Council as a Permanent Observer in May 2013. This report investigates the impacts of Northern Sea Route on the various sectors of Singapore’s maritime industry and how Singapore can transform upcoming challenges into opportunities to stay relevant as a recognised International Maritime Centre. The research was carried out through gathering articles from recognised sources. It was subsequently substantiated through surveys and interviews with industry players. This way, we were able to get an all-rounded view of the subject from both scholarly articles and practical industry players. It is found that, indeed, given the uncertainty of the Arctic conditions, shipping and oil drilling in Arctic Ocean may not be as simple as it seems. It will take many years before these developments materialise. As long as Arctic is not navigable, it is expected that Singapore’s status as an International Maritime Centre would not be affected in the next 10 years.